Muscle Synergies During Walking in Children With Cerebral Palsy: A Systematic Review - Bekius, Annike; Bach, Margit M.; van der Krogt, Marjolein M.; de Vries, Ralph; Buizer, Annemieke I.; Dominici, Nadia (Frontiers in Physiology, 2020)
Background: Walking problems in children with cerebral palsy (CP) can in part be explained by limited selective motor control. Muscle synergy analysis is increasingly used to quantify altered neuromuscular control during walking. The early brain injury in children with CP may lead to a different development of muscle synergies compared to typically developing (TD) children, which might be an underlying factor of abnormal walking patterns. Objective: The overarching aim of this review is to give an overview of the existing studies investigating muscle synergies during walking in children with CP compared to TD children. The main focus is on how muscle synergies differ between children with CP and TD children, and we examine the potential of muscle synergies as a measure to quantify and predict treatment outcomes. Methods: Bibliographic databases were searched by two independent reviewers up to 22 April 2019. Studies were included if the focus was on muscle synergies of the lower limbs during walking, obtained by a matrix factorization algorithm, in children with CP. Results: The majority (n=12) of the 16 included studies found that children with CP used fewer muscle synergies during walking compared to TD children, and several studies (n=8) showed that either the spatial or temporal structure of the muscle synergies differed between children with CP and TD children. Variability within and between subjects was larger in children with CP than in TD children, especially in more involved children. Muscle synergy characteristics before treatment could predict treatment outcomes (n=3). Only minimal changes in synergies were found after treatment. Conclusions: Children with CP use a simpler motor control strategy compared to TD children. The use of muscle synergy analysis as a clinical tool to quantify altered neuromuscular control and predict clinical outcomes seems promising. Further investigation on the use of muscle synergies as a target for development of novel therapies in children with CP is recommended.